Designing the Properties of Probiotic Kefir with Increased Whey Protein Content - Aslı Yiğit Ziolkowski; Paulina Bielska; Dorota Cais-Sokolińska; Gülhan Samur (Fermentation)
This research unveiled new insights on the impact of incorporating whey proteins into kefir produced using three different methods. This aims to improve its quality and health benefits, primarily as a result of optimal proliferation of probiotic bacteria. In the initial part of the experiment, samples were prepared using three different methods (methods 1, 2, and 3) to examine the impact of introducing whey protein on bacterial count, the content of L(+)-lactic acid, lactase activity, and the lactic acid and ethanol levels. The methods differed primarily in the sequence of the inoculation milk with probiotic bacteria stage in the production cycle, as well as incubation time and temperature. No significant differences were found in the number of yeasts and bacteria between samples with and without whey proteins. However, it was revealed that the 5% addition of whey proteins enhanced the number of probiotic bacteria in kefir produced with method 2 (from 4.86 to 5.52 log cfu/mL) and method 3 (from 3.68 to 4.01 log cfu/mL). The second part of the research investigated the impact of whey proteins on firmness, consistency, cohesiveness, viscosity, color, and water activity of kefir. This part focused on testing samples with lower whey protein contents (1 and 3%, w/v). We found that the addition of 1% and 3% whey proteins resulted in decreased firmness, consistency, cohesiveness, and viscosity compared to the control kefir. On the other hand, the addition of 5% whey proteins resulted in increased firmness and consistency compared to the addition of 1% and 3% whey proteins. The addition of whey protein decreased the white index WI of the kefir samples. Overall, our results revealed that incorporating whey protein concentrate (WPC) in the production of probiotic kefir can enhance its health benefits while maintaining its rheological properties and overall quality.